If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying -3x + -16 = 2x + 4 Reorder the terms: -16 + -3x = 2x + 4 Reorder the terms: -16 + -3x = 4 + 2x Solving -16 + -3x = 4 + 2x Solving for variable 'x'. Move all terms containing x to the left, all other terms to the right. Add '-2x' to each side of the equation. -16 + -3x + -2x = 4 + 2x + -2x Combine like terms: -3x + -2x = -5x -16 + -5x = 4 + 2x + -2x Combine like terms: 2x + -2x = 0 -16 + -5x = 4 + 0 -16 + -5x = 4 Add '16' to each side of the equation. -16 + 16 + -5x = 4 + 16 Combine like terms: -16 + 16 = 0 0 + -5x = 4 + 16 -5x = 4 + 16 Combine like terms: 4 + 16 = 20 -5x = 20 Divide each side by '-5'. x = -4 Simplifying x = -4
| sqrtx+10=2 | | (4+1.3)*2.1= | | 15(4y+14)= | | 5x-(-2)=3 | | -2x+9x-4x=0 | | (1-4u+v)(-9)= | | 5(1)-y=3 | | 5x-(0)=3 | | 9-2(5-4)= | | 8d+7d= | | d+d+2+d+4+d+6= | | 32r=10 | | 32=10 | | 10=rt | | 2(3z-2)+8=38 | | 2(2x+4)=-3(5x-3) | | -4(x-8)-7=7(x-6) | | 6(x+2)-8=4x+2(1+x) | | 6x-8=4x+18 | | (9x+20)=28 | | 8-5(x+3)=x-29 | | 105=15+18v | | 3(x+5)-4=6x-3(-4+x) | | 10b+-2=7b-7.4 | | x=31.64165854+-1.536585366y | | (12a-3b-5c)-5(-5a+4b-6c)= | | -23.4/_1/3 | | (x+3)(6x-8)= | | 2x+75=6x-1 | | .16(x-5)=.50(x+6) | | f(x)=x^5+3x^4-2x^2+4x-7 | | 5X^2+3X-X=0 |